2021
DOI: 10.1016/j.ijcard.2021.05.042
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on the consequences of SARS-CoV-2 infection on the heart of young adult competitive athletes: Implications for a safe return-to-play

Abstract: Objectives The COVID-19 pandemic has shocked the sports world because of the suspension of competitions and the spread of SARS-CoV-2 among athletes. After SARS-CoV-2 infection, cardio-pulmonary complications can occur and, before the resumption of sports competitions, a screening has been recommended. However, few data are available and discrepancies exist in the screening modalities. We conducted this prospective study to investigate the incidence of cardiovascular consequences following SARS-CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 38 publications
(66 reference statements)
7
58
2
Order By: Relevance
“…In five studies comprising 268 athletes including study controls CMR was performed; in three studies comprising 897 athletes including study controls echocardiography was performed; in four studies comprising 1968 athletes including study controls both CMR and echocardiography were performed. COVID-19 was diagnosed by real-time reverse transcriptase PCR in seven studies, by antibody testing in two studies and in two studies by one of the two; one study (Cavigli et al 23 ) study did not report diagnostic tests. All included athletes had recovered from SARS-CoV-2 infection, of which 0.1% recovered in-hospital and 99.9% at home.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In five studies comprising 268 athletes including study controls CMR was performed; in three studies comprising 897 athletes including study controls echocardiography was performed; in four studies comprising 1968 athletes including study controls both CMR and echocardiography were performed. COVID-19 was diagnosed by real-time reverse transcriptase PCR in seven studies, by antibody testing in two studies and in two studies by one of the two; one study (Cavigli et al 23 ) study did not report diagnostic tests. All included athletes had recovered from SARS-CoV-2 infection, of which 0.1% recovered in-hospital and 99.9% at home.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Martinez et al, 35 reported six cases of pericarditis/myocarditis (confirmed on CMR) of which four had abnormal echocardiography findings ('small' (not further defined) PE, LVEF 50%, new region wall abnormalities/preserved LVEF and dilated RV). Finally, Cavigli et al 23 reported PE in three athletes with symptomatic SARS-CoV-2 infections, of which one confirmed myopericarditis and two cases of pericarditis.…”
Section: Athletesmentioning
confidence: 97%
“…In these athletes, RTP was also more delayed in comparison to those with cardiac abnormalities but without arrhythmias. Surprisingly, few small studies [6] included ET as mandatory in the screening for RTP after SARS-CoV-2 infection, despite it being well known that effort may unmask arrhythmias not present at rest [11]. Additionally, exercise stress testing (e.g., step test) is a fundamental component of the annual pre-participating screening in competitive and professional athletes in Italy, according to FMSI rules approved by the Italian law.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have aimed to determine cardiac risk stratification in athletes over the last two years of the pandemic [2][3][4][5][6][7][8]. However, the relatively small sample sizes of the studies, the single-centered approach, the small number of sport disciplines assessed and the underrepresentation of female athletes limit definitive conclusions and the generalizability of the results obtained to date.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Italian researchers, ninety asymptomatic or mildly symptomatic competitive athletes were involved in different sports. Cardiac consequences of COVID-19 infection were investigated by detailed cardiovascular screening (physical examination, blood tests, spirometry, 12-lead resting ECG, 24-h ambulatory ECG monitoring, echocardiography, CPET) [ 25 ]. Perimyocarditis was found in one case and pericarditis in two cases, instances which are as low as in our study.…”
Section: Discussionmentioning
confidence: 99%